Level of satisfaction of the users in the process of attention before the covid-19 in the Martinez Health Center: Level of satisfaction of the users in the process of attention before the covid-19 in the Martinez Health Center (La U Investiga, 2021)
Health Centres provide first level medical care services, whose main characteristic is the participative relationship with the population, guaranteeing a service of equity, social solidarity and effectiveness. However, the health emergency has led to drastic changes in first level medical care, causing a crisis. Therefore, the present investigation determined the levels of user satisfaction in the process of Covid-19 care at the Martínez Health Centre, using a quantitative and descriptive field approach, which took as a sample 84 Covid-19 cases attended during the period March - September 2020, to whom a survey was applied based on the SERVQUAL (Quality Service) questionnaire that measures the levels of satisfaction under the dimensions of reliability, responsiveness, safety, empathy and tangibles, making a comparison between expectations and perceptions. This has allowed us to determine a satisfaction level of 45% in the reliability dimension, 34% in responsiveness, 70% in safety, 70% in empathy and 86% in the tangibles dimension. The result is a 61% level of satisfaction among the users attended to by Covid-19 at the Martínez Health Centre, with a 39% level of dissatisfaction, which is considered to be within the acceptable range, thus establishing aspects to be improved, such as reducing waiting times, respecting the order of arrival to be attended to, and the supply of the pharmacy.
Keywords: Care process; body image; secuelles Covid-19; User